Safety, Tolerability and Pharmacokinetics of Single and Repeat Doses of Vixotrigine in Healthy Volunteers. Issue 4 (13th December 2020) - Naik, Himanshu; Steiner, Deb J.; Versavel, Mark; Palmer, Joanne; Fong, Regan
Abstract : Neuropathic pain affects 6.9–10% of the general population and leads to loss of function, anxiety, depression, sleep disturbance, and impaired cognition. Here, we report the safety, tolerability, and pharmacokinetics of a voltage‐dependent and use‐dependent sodium channel blocker, vixotrigine, currently under investigation for the treatment of neuropathic pain conditions. The randomized, placebo‐controlled, phase I clinical trials were split into single ascending dose (SAD) and multiple ascending dose (MAD) studies. Healthy volunteers received oral vixotrigine as either single doses followed by a ≥ 7‐day washout period for up to 5 dosing sessions (SAD, n = 30), or repeat doses (once or twice daily) for 14 and 28 days (MAD, n = 51). Adverse events (AEs), maximum observed vixotrigine plasma concentration (Cmax ), area under the concentration‐time curve from predose to 24 hours postdose (AUC0–24 ), time to Cmax (Tmax ), and terminal half‐life ( t 1/2), among others, were assessed. Drug‐related AEs were reported in 47% and 53% of volunteers in the SAD and MAD studies, respectively, with dizziness as the most commonly reported drug‐related AE. SAD results showed that Cmax and AUC increased with dose, Tmax was 1–2 hours, and t 1/2 was 11 hours. A twofold increase in accumulation was observed when vixotrigine was taken twice vs. once daily (MAD). Steady‐state was achieved from day 5 onward. These data indicate that oral vixotrigine is well‐tolerated when administered as single doses up to 825 mg and multiple doses up to 450 mg twice daily.